PERILAKU PENGUNJUNG OBJEK WISATA TERHADAP LINGKUNGAN SEKITAR PANTAI GANDORIAH DI KOTA PARIAMAN - Basrafil Ilka; Afdhal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Gandoriah Beach is a major tourist attraction in Pariaman City. This study aims to 1) identify visitors’ behavior toward environmental cleanliness around Gandoriah Beach, and 2) examine visitors’ attitudes toward environmental cleanliness around Gandoriah Beach. This research used a qualitative method with a descriptive approach. Informants were selected using purposive sampling, choosing participants who were visiting Gandoriah Beach at the time. Data were collected through observation, interviews, and documentation. The instrument used in this study was an interview guide containing the main questions posed by the researcher to the research subjects. The results show that visitor behavior at Gandoriah Beach regarding cleanliness is still inconsistent. Although some visitors dispose of trash properly and maintain the cleanliness of the surrounding area, negative behaviors, such as littering and being passive toward cleanliness violations, are still quite dominant. Factors influencing this behavior include weak social norms, low social control, and limited cleanliness facilities. In addition, although visitors have a positive attitude toward the importance of cleanliness and beach preservation, this attitude is not yet fully reflected in actual behavior. Therefore, strengthening social norms, improving facilities, and the active role of managers are key to encouraging more responsible behavior.